THE STUDENTS’ INTEREST IN LEARNING ENGLISH THROUGH TEACHERS’ RAPPORT-BUILDING STRATEGIES - Utami, Andini Putri; Ariyani, Amra; Sofyan, Ryan Rayhana (Universitas Negeri Makassar, 2022)
This study aims to determine students' interest in learning English. This research uses a descriptive qualitative method. The data from this study were collected from the results of observation sheets and interviews. The subjects of this study were two English teachers and the interviews were given to 10 second-grade students of MAN 1 Makassar City selected using purposive sampling with the help of the teachers. The results of this study found that most of the students had an interest in learning English, this was evidenced by their positive responses. In conclusion, through the observation checklist, English teachers at MAN 1 Makassar City implemented the teacher relationship-building strategy for students' interests and the results of observations for students also found that most students were interested in learning English when the teacher implemented the strategy and most of the students interviewed also had a positive response about their interest in learning English. Therefore, the strategy of building teacher relationships for the benefit of students is very important and useful in the teaching-learning process, especially in English.